Working in lockdown: the relationship between COVID-19 induced work stressors, job performance, distress, and life satisfaction - Kumar, Parul; Kumar, Neha; Aggarwal, Priti; Yeap, Jasmine A.L. (Current psychology (New Brunswick, N.J.), 2021)
Background & aim In the wake of COVID-19, organizations all over India have closed their premises and shifted to work from home policy to curb the further spread of the virus. This has led to increased stress and anxiety among employees, which explicably affects their satisfaction with life. Thus, the present study analyses the effect of COVID-19 induced stressors (role overload, lifestyle choices, family distraction, and occupational discomfort) on employees’ distress levels and job performance. Subsequently, the impact of such distress and job performance on the employees’ life satisfaction is analyzed during the lockdown period. Methodology Data was collected from 433 working professionals of private and public organizations in the Delhi and NCR region of India during India’s third and fourth phase of lockdown via a survey, which was distributed online. Partial least squares structural equation modelling was applied first to establish the validity of this study’s model (measurement model validity) and subsequently test the hypothesized relationships in the model (structural model). Results The COVID-19 induced stressors, i.e., role overload, lifestyle choices, and occupational discomfort, were significant predictors of distress during the lockdown. It has been found that role overload and change in lifestyle choice did not significantly affect job performance. Family distraction, occupational discomfort, and distress were significant in impacting job performance, with distress being the most significant one. During the COVID-19 pandemic, life satisfaction has reduced due to a significant increase in distress levels and lowered job performances.